Opportunities and Challenges in Implementing Information Technology Innovations in the Indonesian Education Sector - Hadiningrat, K.P. Suharyono S.; Silalahi, Verry Albert Jekson Mardame; Wardani, Febri Pramudya (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research explores the opportunities and challenges in implementing information technology (IT) innovations in Indonesia's education sector. The study examines key variables such as infrastructure, internet access, and teacher training, using qualitative methodologies including case studies and literature reviews. Data were collected from various sources over the past decade. Findings highlight that while IT can enhance education quality and access, particularly through e-learning and digital tools, significant barriers remain due to Indonesia's geographical diversity and unequal infrastructure. The research suggests strategies for overcoming these challenges, such as accelerated infrastructure development, increased research funding, and comprehensive teacher training programs. These insights aim to inform policy and practice, enhancing IT integration in Indonesian education.